Statistical Analysis of the Development of Ukraine’s Construction Industry in 2020–2024 and Organizational-Technological Implications - Shoniia, I. D.; Olkhovyk, S. M. (Science and Transport Progress, 2025)
Purpose. To provide a coherent and accessible assessment of changes in Ukraine’s construction sector during the crisis period; to show how these shifts affected output, demand structure, the labor market, and firms’ financial performance; and to derive practical guidance for organizing reconstruction. Methodology. The study combines general scientific approaches with transparent statistical procedures. Comparisons are conducted on a harmonized, fixed territorial basis, excluding temporarily occupied territories and areas of active hostilities. We employ fixed-base and chain indices to track dynamics, a structural analysis of shares by construction product type, and a decomposition of sub-sector contributions to changes in aggregate indicators. Sensitivity checks are performed for the choice of base period and weighting choices, complemented by logical cross-checks of totals. Findings. We identify a sequence of contraction, adaptation, and gradual recovery. Evidence shows a persistent shift in demand from residential building towards engineering infrastructure and industrial facilities. The role of small and micro enterprises in employment increases, while financial outcomes diverge notably across activity types and firm-size groups. The findings also underline reliance on public reconstruction programs and the importance of transparent management of schedules, costs, and logistics. Originality. We propose a concise yet rigorous analytical framework that separates organic recovery from statistical base effects and changes in coverage. The nature of structural shifts is clarified; quantitative estimates of sub-sector contributions are produced; and the use of a fixed territorial basis is justified for correct intertemporal comparison. Practical value. The results support the prioritization of critical-infrastructure projects, realistic planning of resources and supply chains, and the design of contracting models with strengthened control of risk and cost. The analysis further substantiates the deployment of building information modelling with time and cost dimensions, the use of modular and industrialized solutions, flexible subcontracting arrangements, and digital monitoring—measures that enhance project controllability and coordination among stakeholders in a volatile environment.